Structure of discadenine, a spore germination inhibitor from the cellular slime mold, dictyosteliumdiscoideum. - Abe, H.; Uchiyama, M.; Tanaka, Y.; Saitô, H.
In the previous papers, we reported the isolation, purification and some nature of a potent spore germination inhibitor from the cellular slime mold, Dictyostelium discoideum, 1 and subsequently presented the partial structure consisting of 6-(3-methyl-2-butenylamino)purine moiety and an unknowna-amino acid residue which was most possibly substituted at the N-3 position of the purine ring. 2 Recently we have developed an improved isolation procedure described herein for structure determination. In this paper, we wish to present the structure of the inhibitor which we name discadenine, as 3-(3-amino-jcarboxypropyl)-6-(3-methyl-2-butenylamino)purine(I).
Keywords: POVIDONE IODINE